2022
DOI: 10.1093/geroni/igac040
|View full text |Cite
|
Sign up to set email alerts
|

Findings From Talking Tech: A Technology Training Pilot Intervention to Reduce Loneliness and Social Isolation Among Homebound Older Adults

Abstract: Background and Objectives Social isolation and loneliness are common among older adults and associated with negative health outcomes including cognitive decline, depression, suicide ideation, and mortality. Information and communication technology interventions are often used to combat loneliness and social isolation; however, homebound older adults face barriers to access. This study reports findings from a novel pilot intervention, called Talking Tech, designed to reduce loneliness and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The review comprised 17 research studies. 35 – 51 Of the papers, nine were qualitative studies, and eight were mixed-method studies with an analysis of qualitative data. The sample size ranged from 2 to 90.…”
Section: Resultsmentioning
confidence: 99%
“…The review comprised 17 research studies. 35 – 51 Of the papers, nine were qualitative studies, and eight were mixed-method studies with an analysis of qualitative data. The sample size ranged from 2 to 90.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the use of ICT, smartphones, and video calls did not have a significant impact on loneliness. To date, few studies have looked at the use of ICT and loneliness in older adults [ 24 , 25 , 48 ]. For instance, a cross-sectional study conducted in Germany with this population showed that individuals who used web-connected ICT present with lower levels of loneliness [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Living with children due to unemployment or divorce or caring for grandchildren could be some of these protective factors. There are hardly any studies looking at the use of new technologies as protective tools against loneliness [ 21 , 24 , 25 ]. There is no relevant research on community-dwelling older adults that shows the relationship between feelings of loneliness and the use of telephones or smartphones to make video calls or engage in social contact through virtual social networks.…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness, a multifaceted public health issue, extends its impact beyond the realm of emotional well-being, significantly influencing physical and mental health, as well as the overall quality of life ( 1 , 2 , 4 , 5 ). The dynamics of loneliness, along with its determinants, exhibit substantial variation across different regions and countries, necessitating a deeper understanding of its global and regional nuances ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, loneliness emerges as a significant predictor of depressive symptoms and a key determinant in the erosion of quality of life, even when other factors are accounted for ( 12 , 13 ). Moreover, its association with adverse health outcomes such as cognitive decline, depression, and increased mortality further underscores its severity ( 5 ).…”
Section: Introductionmentioning
confidence: 99%